Multiple mechanisms shape the relationship between pathway and duration of focal seizures. Issue 4 (6th July 2022) - Schroeder, Gabrielle M; Chowdhury, Fahmida A; Cook, Mark J; Diehl, Beate; Duncan, John S; Karoly, Philippa J; Taylor, Peter N; Wang, Yujiang
Abstract: A seizure's electrographic dynamics are characterized by its spatiotemporal evolution, also termed dynamical 'pathway', and the time it takes to complete that pathway, which results in the seizure's duration. Both seizure pathways and durations have been shown to vary within the same patient. However, it is unclear whether seizures following the same pathway will have the same duration or if these features can vary independently. We compared within-subject variability in these seizure features using (i) epilepsy monitoring unit intracranial EEG (iEEG) recordings of 31 patients (mean: 6.7 days, 16.5 seizures/subject), (ii) NeuroVista chronic iEEG recordings of 10 patients (mean: 521.2 days, 252.6 seizures/subject) and (iii) chronic iEEG recordings of three dogs with focal-onset seizures (mean: 324.4 days, 62.3 seizures/subject). While the strength of the relationship between seizure pathways and durations was highly subject-specific, in most subjects, changes in seizure pathways were only weakly to moderately associated with differences in seizure durations. The relationship between seizure pathways and durations was strengthened by seizures that were 'truncated' versions, both in pathway and duration, of other seizures. However, the relationship was weakened by seizures that had a common pathway, but different durations ('elasticity'), or had similar durations, but followed different pathways ('semblance'). Even in subjects with distinct populations of short and long seizures, seizure durations were not a reliable indicator of different seizure pathways. These findings suggest that seizure pathways and durations are modulated by multiple different mechanisms. Uncovering such mechanisms may reveal novel therapeutic targets for reducing seizure duration and severity. Abstract : Schroeder et al . investigated the relationship between epileptic seizure duration and the sequence of activity patterns during a seizure (termed 'seizure pathway'). They found multiple mechanisms modulating the relationship, and concluded that the duration of a seizure is generally not a reliable indicator of its pathway. Graphical Abstract: Graphical abstract